(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
The damping ratio is an important parameter in dynamic analyses and plays a key role in the design of building structures. Elastic response spectra are widely used in this design to describe the earthquake action in specific site classes. 5% damped response spectra are generally used for most of the conventional structures. However, other types of structures may not have a damping ratio of 5% and can have much lower or much larger damping ratios. The damping ratio is recommended at about 5% for concrete structures whereas it is estimated at 2% for steel structures. Tall slender buildings may have much lower damping ratios and low-rise buildings may be designed using much larger damping ratios than 5%. For these types of buildings, elastic response spectra are modified to account for different levels of damping ratios. This study proposes the damping modification factors (DMFs) which are computed using 5% response spectra as the benchmark. A strong ground motion set has been selected for the stiff site class and the displacement, pseudo-velocity, and pseudo-acceleration response spectra have been computed for single-degree-of-freedom (SDOF) systems. DMFs have been obtained in terms of these spectra and 3%, 10%, 20%, and 30% damping ratios have been considered. Variations of DMFs with different damping ratios have been obtained graphically. It can be seen from the results that DMFs are sensitive to the vibration period of the SDOF system.